Reflexões sobre a violência em Racionais MC’s - Rodrigues, José Eduardo Vissoto [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This study analyzes violence through the lens of the lyrics by the group Racionais MC’s, considering rap as a legitimate historical source for understanding the social dynamics of Black and peripheral youth in Brazil. The main objective is to demonstrate how the group articulates narratives of resistance, identity, and social critique, particularly regarding police and prison violence. The methodology combines approaches from Social History with cultural criticism and musical analysis, especially based on the works of Marcos Napolitano and Marcos Gruchka da Silva, in order to examine both the context and the lyrical and aesthetic content of the songs. The results show that Racionais MC’s compositions not only portray the reality experienced by thousands of Black youth in the peripheries but also offer critical interpretations that challenge official discourses on security, citizenship, and marginalization. The study concludes that rap, as an Afro-diasporic cultural practice, functions as a tool for historical and political reflection, essential for understanding exclusion, resistance, and the production of knowledge within peripheral communities. Additionally, the research highlights rap’s pedagogical potential in the classroom and its contribution to the recognition of Black and popular epistemologies in the field of History.

O presente trabalho analisa a violência sob a ótica das letras do grupo Racionais MC’s, considerando a relevância do rap como uma fonte histórica legítima para compreender as dinâmicas sociais da juventude negra e periférica no Brasil. O estudo tem como objetivo demonstrar como o grupo articula narrativas de denúncia, resistência e identidade nos seus discursos musicais, em especial sobre as violências policial e prisional. A metodologia utilizada combina abordagens da História Social com aportes da crítica cultural e da análise musical, em especial os referenciais de Marcos Napolitano e Marcos Gruchka da Silva, a fim de explorar tanto o contexto quanto o conteúdo lírico e estético das canções. Os resultados revelam que as composições dos Racionais MC’s não apenas retratam a realidade vivida por milhares de jovens negros nas periferias, mas também produzem interpretações críticas que tensionam os discursos oficiais sobre segurança, cidadania e marginalidade. Conclui-se que o rap, enquanto prática cultural afro-diaspórica, constitui-se como instrumento de reflexão histórica e política, sendo fundamental para compreender as formas de exclusão, resistência e produção de saberes nas comunidades periféricas. Além disso, a pesquisa aponta o potencial pedagógico do rap em sala de aula e sua contribuição para a valorização de epistemologias negras e populares no campo da História.
Reflections about violence in Racionais MC’s
Keywords: Hip-hop; Racionais MC's; Rap; Violência; Violence